Análise de Mobilidade Urbana em Diferentes Estratos Sociais a partir de uma Rede de Telefonia Móvel - Rodrigues, Francielly; Xavier, Carolina R.; Evsukoff, Alexandre G.; Ziviani, Artur; Vieira, Vinícius da F. (Anais do Workshop de Computação Urbana (CoUrb); 2018: Anais do II Workshop de Computação Urbana, 2018)
Urban mobility of a citizen can be understood as the sequences of trips followed by him. The social classes in which individuals are contextualized, however, denote a significant factor for the spatial organization of a city. The goal of this study is to investigate mobility patterns and analyze characteristics of social classes in the Rio de Janeiro State using cell phone data together with census data, in order to analyze not only the movement of the population as a whole but also to make comparisons between different social classes. It is clear that the classes follow the same pattern of distances traveled daily, but with higher classes traveling shorter distances. Another analyzed topic was the average number of calls, whose probability distribution follows a heavy tail, a frequent behavior in communication analysis. The main contribution of the present study is the developed methodology, which can work for several georreferenced databases, by simply adjusting it to the desired granularity.